Can you take another pic of it because it is blurry
Difference=subtract sum=add. just answering so you don't waste points :-)
Answer:
![k=-\frac{1}{4}](https://tex.z-dn.net/?f=k%3D-%5Cfrac%7B1%7D%7B4%7D)
Step-by-step explanation:
we have
Line 1
![y=4x+1](https://tex.z-dn.net/?f=y%3D4x%2B1)
Equation in slope intercept form
The slope is equal to
![m_1=4](https://tex.z-dn.net/?f=m_1%3D4)
Line 2
![y-kx=10](https://tex.z-dn.net/?f=y-kx%3D10)
![y=kx+10](https://tex.z-dn.net/?f=y%3Dkx%2B10)
Equation in slope intercept form
The slope is equal to
![m_2=k](https://tex.z-dn.net/?f=m_2%3Dk)
we know that
If two lines are perpendicular, then their slopes are opposite reciprocal (the product of the slopes is equal to -1)
so
![m_1*m_2=-1](https://tex.z-dn.net/?f=m_1%2Am_2%3D-1)
substitute
![(4)(k)=-1](https://tex.z-dn.net/?f=%284%29%28k%29%3D-1)
![k=-\frac{1}{4}](https://tex.z-dn.net/?f=k%3D-%5Cfrac%7B1%7D%7B4%7D)
x=3y
Switch sides
3y=X
Divide 3 both sides to get
T= x/3
Answer:
1
Step-by-step explanation:
using PEDMAS(parentheses, exponents, division, multiply, addition, subtraction) to solve the problem
First we multiply (4)(-3)
(4)(−3)−5−3(−6)
Then multiply -3(-6)
(-12)-5-3(-6)
=-12-5+18
subtract 12-5
-12-5+18
=-17+18
Adding -17+18 gives us 1.
Therefore, (4)(−3)−5−3(−6) is 1.